The acid-base transport proteins NHE1 and NBCn1 regulate cell cycle progression in human breast cancer cells. Issue 9 (3rd May 2018) - Flinck, Mette; Kramer, Signe Hoejland; Schnipper, Julie; Andersen, Anne Poder; Pedersen, Stine Falsig
ABSTRACT: Precise acid-base homeostasis is essential for maintaining normal cell proliferation and growth. Conversely, dysregulated acid-base homeostasis, with increased acid extrusion and marked extracellular acidification, is an enabling feature of solid tumors, yet the mechanisms through which intra- and extracellular pH (pHi, pHe ) impact proliferation and growth are incompletely understood. The aim of this study was to determine the impact of pH, and specifically of the Na + /H + exchanger NHE1 and Na +, HCO3 − transporter NBCn1, on cell cycle progression and its regulators in human breast cancer cells. Reduction of pHe to 6.5, a common condition in tumors, significantly delayed cell cycle progression in MCF-7 human breast cancer cells. The NHE1 protein level peaked in S phase and that of NBCn1 in G2/M. Steady state pHi changed through the cell cycle, from 7.1 in early S phase to 6.8 in G2, recovering again in M phase. This pattern, as well as net acid extrusion capacity, was dependent on NHE1 and NBCn1. Accordingly, knockdown of either NHE1 or NBCn1 reduced proliferation, prolonged cell cycle progression in a manner involving S phase prolongation and delayed G2/M transition, and altered the expression pattern and phosphorylation of cell cycle regulatory proteins. Our work demonstrates, for the first time, that both NHE1 and NBCn1 regulate cell cycle progression in breast cancer cells, and we propose that this involves cell cycle phase-specific pHi regulation by the two transporters.